Analogical reasoning, control and executive functions: A developmental investigation with eye-tracking - Thibaut, Jean-Pierre; French, Robert M. (Cognitive development, 2016)
•First contribution to study the development of analogical reasoning with eye-tracking. Adults follow a projection-first strategy (study A:B, then C:D). Children organize their search around C.•No evidence of alignment (i.e., A-C and B-D saccades) in the A:B:C:D paradigm.•Children have difficulties to inhibit the main goal of the task (“what goes with C”).•Errors result from a less efficient strategy starting at the beginning of the trial. We use eye-tracking to study the development of analogical reasoning in 5-year-olds, 8-year-olds, adolescents and adults in the A:B:C:D paradigm. We observed significant differences between groups in the way they explored the space of possible answers to analogy problems. Looking times showed that adults first studied the possible relations between A and B and, thereafter, they moved to C and the solution set. Children, by contrast, tended to start with the C item and organized their search around this item. Children's and adults' saccade patterns differed at the beginning and the end of the trial. Children monitored their search less efficiently than adults (fewer saccades from the solution set to the A–B pair at the end of the trial). Looking patterns associated with errors and correct trials also differed from the start of the trial, suggesting that different search strategies lead to different outcomes. Results are contrasted with current models of analogical reasoning and are discussed in terms of the interaction between the development of executive functions and the control and integration of the information pertaining to the analogy problem.